160k views
1 vote
PLEASE HELP

Look at the proof showing sin^4x=3-4cos2x+cos4x/8. Which expression will complete the fourth step of the proof?
sin^4x=(sin^2x)^2
sin^4x=(1-cos2x/2)^2
sin^4x=1-2cos2x+cos^22x/4
sin^4x=?
A.) 1-2cos2x+(1+cos4x/2)/4
B.)1-2cos2x+1+cos4x/4
C.)1-2cos2x+(1+cos2x/2)/4
D.)1-2cos2x+1-cos2x/4

User Kizoso
by
5.8k points

1 Answer

5 votes
Correct Answer: Option A

The next step in simplification will be to convert the squared term so that it no longer contains a square.

So, we are to simplify the term
cos^(2)(2x)

Using the half-angle identity we can write:


cos^(2)(2x)= (1+cos(4x))/(2)

Using this value, the equation becomes:


sin^(4)x=1-2cos(2x)+ ( (1+cos(4x))/(2) )/(4)

Therefore, option A is the correct answer.
User Tawana
by
5.7k points